Acute oxalate nephropathy associated with herbal remedies - Bahman Bashardoust; Mojgan Asgari (Society of Diabetic Nephropathy Prevention, 2022)
The use of herbal remedies has grown in recent years, largely due to their increased production and the media advertisements which target their use for the cure of almost all symptoms. Herbal remedies have also become popular in multi-plant forms and have recently become available in both industrial and condensed formulations, with higher doses being administered. We report a 68-year-old woman presenting with symptoms of flank pain, nausea, vomiting, anuria, and hematuria. She has history diabetes mellitus, hypertension and use of herbal including Achillea millefolium and Thymus migricus, Nasturtium for the last four months. Kidney biopsy was performed and was diagnosed with oxalate nephropathy. After the use of herbals was stopped, creatinine levels returned toward normal value in the following months with no complications. Herbal remedies would cause severe organ failures if administered in high-doses and should be considered as a possible cause in patients presenting with AKI.